"Lords of the World": Writing Gender and Imperialism on Northern Space in C.C. Vyvyan's Artic Adventure - Smyth, Heather (Studies in Canadian Literature, 1998)
C.C. Vyvyan's travel book Arctic Adventure (1961) marks a transition from centuries of Arctic discovery and exploration narratives. Vyvyan manipulates her traveling and writing personae in a genre that has historically been masculine, and she resists the imperial baggage that traditionally accompanies travel writing. In this movement between the roles of heroic explorer and curious observer, Vyvyan exemplifies T.D. MacLulich's categorization of emplotment in Canadian exploration narratives.